2018
DOI: 10.5194/acp-18-2821-2018
|View full text |Cite
|
Sign up to set email alerts
|

Dome effect of black carbon and its key influencing factors: a one-dimensional modelling study

Abstract: Abstract. Black carbon (BC) has been identified to play a critical role in aerosol–planetary boundary layer (PBL) interaction and further deterioration of near-surface air pollution in megacities, which has been referred to as the “dome effect”. However, the impacts of key factors that influence this effect, such as the vertical distribution and aging processes of BC, as well as the underlying land surface, have not been quantitatively explored yet. Here, based on available in situ measurements of meteorology … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
108
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 82 publications
10
108
1
Order By: Relevance
“…Aerosols in the atmosphere could directly or indirectly influence the radiation balance of the Earthatmosphere system and hence regional or global climate change (Ackerman et al, 2004;Bond et al, 2013;Boucher et al, 2013;Menon et al, 2002). Recent studies have found that the impact of aerosols, particularly absorption aerosols like black carbon (BC) and dusts, to solar radiation is also important to the development of planetary boundary layer (PBL) and the air quality within the PBL Liu et al, 2016;Z. Wang et al, 2018;Wilcox et al, 2016;Yang, Russell, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aerosols in the atmosphere could directly or indirectly influence the radiation balance of the Earthatmosphere system and hence regional or global climate change (Ackerman et al, 2004;Bond et al, 2013;Boucher et al, 2013;Menon et al, 2002). Recent studies have found that the impact of aerosols, particularly absorption aerosols like black carbon (BC) and dusts, to solar radiation is also important to the development of planetary boundary layer (PBL) and the air quality within the PBL Liu et al, 2016;Z. Wang et al, 2018;Wilcox et al, 2016;Yang, Russell, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Li, Guo, et al, 2017;Petäjä et al, 2016;Quan et al, 2013). Second, the solar absorption aerosols in the atmosphere could heat the atmosphere by trapping solar energy and result in strong heating in upper PBL or around the PBL top, which change the vertical temperature stratification and further suppress the development of PBL Z. Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2016), which efficiently heated the surrounding air near 8 km. Previous modelling and observation studies has emphasized the importance of upper-air aerosols in changing temperature stratification because of more incident solar radiation and less efficient vertical heat exchange (Samset et al, 2014;Wang et al, 2018). In this case, BB and dust aloft caused by frontal system were expected to exert important role in changing the air temperature in MLT.…”
Section: Meteorological Feedback Of Mixed Pollutantsmentioning
confidence: 98%
“…CC BY 4.0 License. radiative feedback (Hansen et al, 1997;Li et al, 2011;IPCC, 2013;.Our previous works found how the air pollution-boundary layer feedback changed the weather and in turn how the modified meteorological conditions enhanced the accumulation of air pollution (Ding et al, 2013a;Liu et al, 2016;Ding et al, 2017;Wang et al, 2018).…”
Section: Meteorological Feedback Of Mixed Pollutantsmentioning
confidence: 98%